Análisis de la planta turística, oferta alojamiento del cantón Saquisilí. - Córdova Caizachine, Juan Daniel (2020)
This project work proposed the creation of a catalogue of the tourist plant in Saquisili Canton, which is located in Cotopaxi Province,6 km from Latacunga Canton.It was carried out an information survey on the tourist offer in accommodation. Also, visits were made to the four parishes of the canton For the execution of the first objective, information was collected from bibliographic sources and field trips, through the revision of PDOT (2015), the official website of GAD, INEC (2014) and others which allowed to obtain the diagnosis of the current situation of the place. In addition, the data were analyzed and it was found that Cochapamba is the parish with the highest index of population with indigenous identity. The primary economic structure of this parish is based on agriculture, livestock and forestry. People of this place use one third of the land to carry out these activities. For this reason, through the commerce that is carried out in its squares, they obtain economic benefits and at the same time it is a tourist attraction in the town. On the other hand, the canton keeps its cultural identity alive through folklore and various festivities that attract national and foreign tourists. It was done an inventory by using data sheet elaborated by the students of Engineer Ecotourism Major This sheet was applied to the administrators or managers of each lodging. The data sheet included general data such as category, services, infrastructure, equipment and so on. To categorize, the Regulation of Tourist Accommodations (2015) was revised, in order to verify the information given by the administrator of the place.. As a result, a total of 5 establishments were obtained, presenting the following category: a hotel, a hostel, an inn, a resort and a cabin. All the information was systematized and shown in the tourist accommodation catalogue, which has the following: services, georeferencing, prices, address, contacts, social networks and photographs.